Abscopal regression following SABR for non-small-cell-lung cancer: A case report. Issue 1 (2nd January 2017) - Cong, Yang; Shen, Ge; Wu, Shikai; Hao, Ruimin
ABSTRACT: Out-of-field tumor response, which is also called abscopal effect, bystander effect, or non-target effect, can be regarded as localized irradiation induced systemic antitumorigenic effects, indicating shrinkage of a tumor distant from the irradiated site. Although abscopal effect has been documented in several tumor types, it is a very rare phenomenon which is clinically reported in non-small-cell-lung carcinoma (NSCLC). Herein, we present a rare case of patient with NSCLC with 2 lesions in the upper lobe of left lung who, after receiving stereotactic ablative radiation therapy (SABR) to one of the tumors, had an apparent spontaneous regression of the other mass in the lung, suggestive of a radiation-induced abscopal effect.